PCR Expression Analysis Of the Estrogeninducible Gene Bcei in Gastrointestinal and Other Human Tumors. Issue 1 (1994) - Wundrack, Iris; Müllenbach, Roman; Welter, Cornelius; Seitz, Gerhard; Blin, Nikolaus
Abstract : A polymerase chain reaction (PCR) assay was developed to test for tumor cell specific expression of the BCEI gene. This new marker gene, reported at first for human breast cancer, was found specifically active in various gastrointestinal carcinomas by previously applying immunohistochemistry and RNA (Northern blot) analysis. Presently, by using reverse transcription -PCR analysis, a series of primary tumor tissues and established tumor cell lines were testcd for BCEI transcription. This approach was compared to immunostaining achieved by an antibody directed against the BCEI gene's product. The result demonstrate the superior sensitivity of PCR by indicating the gene' s expression in cases where immunohistochemical testing remained negative.